U-Th dating, taphonomy, and taxonomy of shell middens at Klasies River main site indicate stable and systematic coastal exploitation by MIS 5c-d - Wurz, Sarah; Pickering, Robyn; Mentzer, Susan M. (Frontiers in Earth Science, 2022)
The archaeological record, particularly of shellfish, from Klasies River main site is important in understanding the fluctuating nature of coastal occupational patterns and changing coastal ecologies. Here, microstratigraphic analyses generate new information about the taphonomy of shell bearing deposits from the Later Stone Age to the MSA l period that in turn provide a broader context for middening at the site. A wide range of syndepositional taphonomic processes related to human activities, as well as post-depositional effects include burning, fragmentation and compaction, chemical alteration, and cementation. Despite such issues influencing recovery, shellfish data are informative and are presented from three layers of the Witness Baulk: Shell Midden One (SMONE), Black Occupational Soils (BOS) and Silty Black Soils (SBLS). These coarse shell midden deposits exhibit visible decalcification coupled with cementation with secondary carbonate formation, in association with conditions of high moisture and soft sedimentation deformation of the underlying sediments of SBLS. This section of the stratigraphy is for the first time chronologically anchored using U-Th dating of speleothems associated with a hiatus after the deposition of BOS. The three ages, 110,060 ± 1,100 years, 109,800 ± 970 and 106,000 ± 2,100 place the BOS layer as the base of the SASL sub-member at older than 110 ka, making the underlying middens from the LBS member even older. The zooarchaeological analyses of the three layers indicate coastal ecological changes from more sheltered conditions prior to the hiatus with exploitation of alikreukel and brown mussel predominant. Before 110 ka, in BOS and SBLS, more exposed coastal conditions occurred, and the diversity of exploited shellfish increased. SMONE and BOS are associated with MSA ll/Mossel Bay lower lithic technology, and SBLS with MSA l technology, indicating asynchronous coastal ecological and technological changes. The MIS 5c-d evidence for early coastal occupation at KRM provides more detail for the period during which coastal occupation became stable and systematic on the South African coast, and puts Klasies River main site amongst the handful of sites with shell bearing deposits that occur prior to 110 ka in South Africa.